CONVERSION OF NORMAL HEXANE AND METHYLCYCLOPENTANE INTO BENZENE BY USING REFORMING CATALYST - A.S. Nasution; E. Jasjfi (Scientific Contributions Oil and Gas, 1985)
As the significant amount of paraffins and naphthenes in the reforming feedstock, the conversion of these hydrocarbons to aromatic in the catalytic reforming process thus plays an important role. An experiment has been carried out to study the reaction rate of normal hexane and methylcyclopentane into benzene by using reforming catalyst